Accountability of Village Fund Management: A Qualitative Study in Ketaren Village - Linda Wahyu Marpaung; Susan Grace V. Nainggolan; Jefri Jefri (Journal of Accounting, Management, Economics, and Business (ANALYSIS), 2026)
Purpose – This study aims to describe and analyze the accountability of Village Fund management in Ketaren and to identify the factors that support and hinder the realization of accountability. Methodology – This study employs a descriptive qualitative approach. Data were collected through semi-structured interviews, observation, and document review involving four purposively selected informants. Data were analyzed using the interactive model of Miles and Huberman. Findings – Accountability of Village Fund management in Ketaren Village has generally been carried out in accordance as confirmed by the Village Head and corroborated by the Village Secretary. The Village Head stated that the Village Fund allocation has greatly benefited the community, the Village Secretary stated that administrative and reporting processes ran well and on time without obstacles, the BPD Chairperson stated that the oversight function had been carried out well, and the community leader stated that the Village Head, who has served three terms, has performed his duties well and is highly attentive to community needs. The only inhibiting factor identified is external in nature. Novelty – This study shows that, unlike prior studies that mainly report internal-technical obstacles, the accountability constraints in Ketaren Village originate from an external, structural source, namely national fiscal policy. Significance – The findings are useful for the Ketaren Village government in sustaining good governance practices, for policymakers concerned with the allocation of Village Fund transfers, and for future researchers examining village financial accountability.